Nivolumab versus docetaxel in a predominantly Chinese patient population with previously treated advanced non-small cell lung cancer: 2-year follow-up from a randomized, open-label, phase 3 study (CheckMate 078). (February 2021) - Lu, Shun; Wang, Jie; Cheng, Ying; Mok, Tony; Chang, Jianhua; Zhang, Li; Feng, Jifeng; Tu, Hai-Yan; Wu, Lin; Zhang, Yiping; Luft, Alexander; Zhou, Jian-ying; et al.
Highlights: Long-term data on 2 L nivolumab in Asian patients with advanced NSCLC are scarce. CheckMate 078 assessed 2 L nivolumab in a predominantly Chinese NSCLC population. At 2 years, overall survival remained longer with nivolumab versus docetaxel. Nivolumab maintained a favorable safety profile with lower rates of TRAEs. Data were consistent with long-term results from global studies. Abstract: Background: In the phase 3 CheckMate 078 study, nivolumab showed significant overall survival (OS) benefit and superior tolerability versus docetaxel in a predominantly Chinese patient population with non-small cell lung cancer (NSCLC). However, data on long-term outcomes with immunotherapy in Asian patients are limited. We report 2-year efficacy and safety data. Methods: Patients with advanced/metastatic NSCLC and disease progression after platinum-doublet chemotherapy were randomized 2:1 to nivolumab (3 mg/kg every 2 weeks; n = 338) or docetaxel (75 mg/m 2 every 3 weeks; n = 166) until progression, unacceptable toxicity, or other protocol-defined reasons. The primary endpoint was OS; secondary endpoints included progression-free survival, objective response rate, and safety. Results: After 25.9 months minimum follow-up, 21 patients (6 %) remained on nivolumab versus 0 on docetaxel. Median OS was 11.9 months with nivolumab versus 9.5 months with docetaxel (HR: 0.75; 95 % CI: 0.61–0.93); 2-year OS rates were 28 % versus 18 %, respectively. Survival benefits were observed across a variety of predefined subgroups. At 2 years, 39 % and 0 % of responders had ongoing responses with nivolumab and docetaxel, respectively. Grade 3–4 treatment-related adverse events occurred in 12 % of patients with nivolumab versus 47 % with docetaxel, leading to discontinuation in 4 % and 5 % of patients, respectively. No new treatment-related deaths occurred. Conclusion: At 2 years, nivolumab maintained a favorable safety profile and continued to demonstrate superior OS versus docetaxel in this predominantly Chinese patient population with previously treated NSCLC. These data are consistent with long-term outcomes from the global CheckMate 017/057 studies.